2007
DOI: 10.1645/ge-1159.1
|View full text |Cite
|
Sign up to set email alerts
|

National Seroprevalence of Toxoplasma gondii in India

Abstract: This article reports the first national serological prevalence of Toxoplasma gondii in India. In total, 23,094 serum samples were tested for T. gondii IgG and IgM antibodies with the use of a solid-phase immunocapture ELISA. Antibodies (IgG) were found in 24.3%; IgM antibodies were detected in 2% of the samples. The lowest seroprevalences were in the northern parts of India, with the highest in the south. These data probably reflect the effects of significantly drier conditions and, therefore, a negative impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 8 publications
2
30
1
1
Order By: Relevance
“…In addition, the age in which seroconversion and parasitemia takes place might also play a role. Seroprevalence for T. gondii in Thailand was 17 % [17], comparable to China (14.8 %) [18] and India (24 %) [19], but lower than in Indonesia (58-70 %) [20,21] and higher than in Vietnam (4.2 %) [22]. When compared to the West, seroprevalence for T. gondii in Thailand was lower than in the Netherlands (41 %) and France (75 %), but similar to the US (14-22.5 %) where T. gondii infections represent the most common cause of intraocular infections in PU [1,23].…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the age in which seroconversion and parasitemia takes place might also play a role. Seroprevalence for T. gondii in Thailand was 17 % [17], comparable to China (14.8 %) [18] and India (24 %) [19], but lower than in Indonesia (58-70 %) [20,21] and higher than in Vietnam (4.2 %) [22]. When compared to the West, seroprevalence for T. gondii in Thailand was lower than in the Netherlands (41 %) and France (75 %), but similar to the US (14-22.5 %) where T. gondii infections represent the most common cause of intraocular infections in PU [1,23].…”
Section: Discussionmentioning
confidence: 83%
“…The organism is zoonotically important and up to one-third of the human population in the world is chronically infected (Dubey and Beattie 1988;Tenter et al 2000). A recent national survey revealed that 24.3% of Indian population is exposed to this parasite (Dhumne et al 2007). Postnatal infection in humans occurs through ingestion of undercooked meat containing tissue cysts or through consumption of food or water contaminated with oocysts (Dubey and Beattie 1988;Dubey et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[6] Seroprevalence average of T. gondii infection in India has been reported to be 24.3%, lowest being in the northern parts of India, and highest in the south and seroconversion rate of 1.5% has been reported. [7] The seroprevalence of toxoplasma in Chandigarh area has been reported to be about 5% with more women showing seropositivity than males. [8] Moreover, since only the acute infection during pregnancy is associated with congenital infections, it is important to know the incidence of acute infection during pregnancy.…”
Section: Introductionmentioning
confidence: 99%